Threats and conservation of Paris polyphylla an endangered, highly exploited medicinal plant in the Indian Himalayan Region - ASHISH PAUL1; PADMA RAJ GAJUREL; ARUP KUMAR DAS (Biodiversitas Journal of Biological Diversity, 2015)
Paul A, Gajurel PR, Das AK. 2015. Threats and conservation of Paris polyphylla an endangered, highly exploited medicinal plant in the Indian Himalayan Region. Biodiversitas 16: 295-302. The Indian Himalayan Region is home of numerous globallysignificant medicinal plants. Paris polyphylla Smith is an important medicinal perennial herbaceous species used mostly in traditionalmedicine, having medicinal properties like anticancer, antimicrobial, antioxidant, anti-tumor, cytotoxicity, steroid saponins etc. Thepresent study highlights the uses, population status and threats to P. polyphylla in Arunachal Pradesh. P. polyphylla is distributed intropical to temperate region of South East Asia, particularly in Bhutan, China, India, Laos, Myanmar, Nepal, Thailand and Vietnam. InIndia it is distributed in the state of Arunachal Pradesh, Himachal Pradesh, Jammu and Kashmir, Manipur, Meghalaya, Mizoram,Nagaland, Sikkim and Uttarakhand. In the Eastern Himalayan state of Arunachal Pradesh, the species found to be occurring with distinctmorphological interspecific variations. In the past 5 years the market demand of the species increased tremendously, which ultimatelyled to the over exploitation of the species and traded illegally in heavy quantities. The present study showed very poor populationdensity, which ranged between 0.42 individuals m-2 to 1.48 individuals m-2. While, Importance Value Index of the species rangedbetween 3.37 to 8.45. Because of the unsustainable extraction and poor natural regeneration of the species, wild populations are at riskof extinction and accordingly it has been listed as an endangered species. The rhizome is the primary mode of regeneration, although itregenerate from seeds. Because of the commercial demand of the rhizome, the population of the species may entirely be wiped out ifproper conservation initiatives have not been taken. Effective conservation strategies both in situ and ex situ may help to protect thespecies from its extinction. Inclusion of the species under the priority species list of both the National and State Medicinal Plant Boardsfor cultivation may be helpful for its long term management and conservation. Mass awareness and active involvement of local peoplefor large scale cultivation may reduce the pressure on wild populations. This will meet the market demand and boost the rural economyand will also help in conservation of the species.